Obstetric Hysterectomy and Maternal Survival - Baral, J; Gurung, G; Rana, A; Manandhar, B; Manandhar, R; Sharma, J (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to analyze the cases of obstetric hysterectomy and maternal complications and survival after that. Methods: A retrospective study was carried out from the review of records of the near miss, maternal mortality, cesarean audit and operation theater record of the Department of Obstetrics and Gynaecology, Tribhuvan University Teaching Hospital (TUTH), Kathmandu from 2057-2071 BS. Results: Fourteen maternal survival resulted following total of 19 obstetric hysterectomy, subtotal hysterectomy being the procedure of choice in 11 cases, emergency peripartum hysterectomy (EPH) being performed in abundance (18/19) in comparison to an elective peripartum hysterectomy, which was undertaken in a single case of placenta percreta, and inclusive of latter were four cases of morbid placental adhesion, a placenta increta and two placenta accreta. Eight out of 19 cases had vaginal delivery and rest had cesarean section. Among seven cases of cesarean hysterectomy 3 were done for placenta previa with accreta one case each done for abruptio placentae and placenta accreta and two cases were done for extra placental causes. Among four cases of emergency peripartum hysterectomy (EPH), which were relaparotomy followed by hysterectomy, three cases were done for complication of cesarean section and one done for uterine atonicity. Four cases of spontaneous vaginal deliveries needed peripartum hysterectomy two of them were complicated by morbid placental adhesion placenta increta (1), placental percreta (1), two cases were vaginal birth after cesarean (VBAC). Seven cases of uterine rupture had undergone peripartum hysterectomy. Conclusions: Obstetric hysterectomy is a lifesaving surgical procedure for maternal survival whenever necessary and mandates a quick decision making process, however in consideration of younger age and low parity or nulliparity, the best obstetric governance and services must foresee not to let mothers meet such situation necessitating organ removal and to enjoy potential reproductive life cycle. DOI: http://dx.doi.org/10.3126/njog.v9i2.11759